Pengaruh Beberapa Dosis Biomelioran terhadap Peningkatan Kesuburan Tanah dan Pertumbuhan Jagung di Lahan Suboptimal - W Astiko; M Taufik Fauzi; I Muthahanas (xxxx-xxxx, 2023)
Astiko W, Fauzi MT, Muthahanas I. 2022. The effect of multiple doses of biomaliorant on increasing soil fertility and maize growth in suboptimal land. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang  27 Oktober 2022. pp. 78-87. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Maize is a strategic food commodity after rice, however national maize production is still low. This study aimed to determine the effect of the dose of bioameliorant on increasing soil fertility and maize growth in suboptimal land. The research method uses experimental methods with field experiments. The experimental design used was a randomized block design consisting of six bioameliorant dosage treatments, namely D0: control (without bioameliorant), D1: bioameliorant dose 5 tons/ha, D2: bioameliorant dose 10 tons/ha, D3: bioameliorant dose 15 tons/ha, D4: dose of bioameliorant 20 tons/ha, and D5: dose of bioameliorant 25 tons/ha. The results showed that the dose of bioameliorant treatment of 25 tons/ha could increase soil fertility as indicated by increasing concentrations of total N and available soil P and increasing plant N and P uptake, number of mycorrhizal spores, percentage of root colonization and plant growth. Of the six treatments of bioameliorant dose, the effect of the 25 ton/ha bioameliorant dose treatment was the best in increasing soil fertility and plant growth.